De Jure Determinants of New Firm Formation: How the Pillars of Constitutions Influence Entrepreneurship - Emanuela Carbonara; Enrico Santarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
This paper provides empirical evidence supporting the view that constitutions may influence the organization of economic activities. Dealing with the issue of the institutional determinants of entrepreneurship, it shows that some of the provisions contained in national constitutions are positively and significantly associated to a standard measure of entrepreneurial dynamics, namely the rate of new business density. Using a novel dataset containing the characteristics of the constitutions enacted in the world and a sample of 115 countries, the paper finds that provisions about the right to conduct/establish a business, the right to strike, consumer protection, protection of trademarks, and education promote higher rates of new firm formation.
Keywords: D72; K10; H10; L26; M13; O50; P48; 330